PENGOLAHAN SAMPAH ORGANIK BERBASIS MAGGOT (Black soldier fly) UNTUK MENDUKUNG KEBERLANGSUNGAN ZERO WASTE DI DESA BILOK PETUNG KECAMATAN SEMBALUN KABUPATEN LOMBOK TIMUR - Ramadhani; Abdullah, Baiq Amanda Esya; Fitria; Manaki, Gempar; Antareja, Gde Margin; Haeruni; Hidayat, Janu Wahyu; Sari, Nila Marta; Amalia, Risa (Universitas Mataram, 2024)
West Nusa Tenggara Province faces serious waste management problems. Bilok Petung Village produces around 3 tonnes of waste per day, most of which ends up in the landfill. A zero waste approach using BSF (Black Soldier Fly) could be a solution. The aim of KKN activities in Bilok Petung Village is to explore the process of cultivating BSF (Black Soldier Fly) magots to support the implementation of zero waste. Activity methods include providing BSF cultivation facilities, collecting organic waste, hatching BSF eggs, maintaining BSF, harvesting eggs, processing maggots, and packaging products. The results of the activity show that BSF cultivation is able to process village organic waste into pupae and organic fertilizer with economic value. Pupae can be used as a source of animal protein and organic fertilizer can increase soil fertility. Thus, BSF cultivation has the potential to support the implementation of zero waste in Bilok Petung Village in a sustainable manner.